Hydrogen generation from NaBH4 hydrolysis using Co-B/AlPO4 and Co-B/bentonite catalysts. (2nd October 2017) - Manna, Joydev; Roy, Binayak; Pareek, Devendra; Sharma, Pratibha
Abstract: Aluminium phosphate and bentonite supported Co-B catalyst were synthesized via two step impregnation-reduction method for sodium borohydride hydrolysis. The synthesized catalysts were characterized by XRD, FTIR, XPS, FE-SEM, FE-TEM, BET, ICP-AES techniques and tested for NaBH4 hydrolysis reaction. The results demonstrated that the synthesized supported Co-B catalysts greatly facilitate the NaBH4 hydrolysis reaction. Highest hydrolysis rate observed for Co-B/AlPO4 and Co-B/bentonite catalysts are 6.50 and 3.91 L min −1 g −1, respectively, with 2 wt% NaBH4, 5 wt% NaOH solution at 30 °C. The hydrogen generation rate was found to increase with experimental temperature. Activation energy for the hydrolysis reaction was observed to be 37 and 40.2 kJ mol −1 for Co-B/AlPO4 and Co-B/bentonite catalysts, respectively. Abstract :